The Development of Business Strategy in the Digital Society of Social Media - Ananthi, D; Jenila, S (International Journal of Computer Sciences and Engineering, 2025)
Internet image has been improving day by day, where every activities of a person is concerned with the digital environment. This surfing behaviour of an individual can be monitored and analysed for various purposes. We should be aware that our accessing strategy is a key factor for various companies that leads business growth and the privacy of the user is compromised. Mainly when we are accessing social networks like Facebook, twitter, YouTube and Instagram etc. there are lot of data is being served to the agents of the organization. Accumulating these data, the marketing growth can be analysed. So the user must be known what is happening in the social network. So in this paper we expose how the privacy and knowledge data can be collected from customer and therebycompanies use the customer interaction for their business directly through social media